An Empirical Study on Influence of Specific Bank’s Variable and Macroeconomics on Bank’s Default Risk: The Case of Foreign Exchange Banks in Indonesia - M. Puspitasari, Devy; Febrian, Erie; Anwar, Mokhammad; Sudarsono, Rahmat (International Journal of Psychosocial Rehabilitation, 2020)
Purpose: Risk management is an integral part of a sustainable foreign exchange bank in Indonesia. The purpose of this study was to conduct an empirical investigation and to determine the risk for sustainable management of foreign exchange banks in Indonesia, especially default risk. Design/methodology/approach: The method used in this article is using the logit model. Goodness of fit test used to examine fit model or otherwise. Likelihood, Cox & Snell R Square, and the Hosmer-Lemeshow test were used to verify the model. The Wald statistic is used to examine the effect of each independent variable on the dependent variable. Findings: The findings showed that risk on foreign exchange banks in Indonesia is influenced by specific and macroeconomic variables that affect the performance of foreign exchange banks. Non-performing loans, credit quality, capital requirements, interest rates, and inflation have an effect on the occurrence of default risk in foreign exchange banks in Indonesia. Research limitation/implications: This research uses secondary data from foreign exchange banking statistics for 68 months from July 2011 to February 2017 in Indonesia. Practical implications: This study contributes policy to mitigate risk bank (default risk) that can affect the performance of foreign exchange banks in the challenge of being able to compete on a regional and international scale. Originality/value: In this study, independent variables are divided into the specific bank’s variables (internal variables) and macroeconomics. The internal variables are non-performing loans, capital requirements, credit quality, and bank size. Interest rate and inflation are chosen as macroeconomic variables.